Platform ecology: A user‐centric and relational conceptualization of online platforms. (24th December 2021) - Ibert, Oliver; Oechslen, Anna; Repenning, Alica; Schmidt, Suntje
Abstract: Online platforms provide a technological infrastructure allowing social actors to enact and utilize networks with a global reach. They play important roles as intermediaries and algorithm‐based curators of social interaction. This paper addresses two knowledge gaps: First, while a growing number of empirical studies has deepened our insights into the social dynamics characterizing single platforms, little is known about the multiple ways in which users or user groups combine diverse online offers according to their preferences. Second, the empirical focus has mainly been on online interaction. However, in everyday practices, the online is always situated in offline practices. It is thus necessary to understand the complex interdependencies of online and offline spheres. This paper therefore aims to develop an ecological heuristic that positions the user(s) and their practices center stage in the analysis and to elucidate the on/offline opportunity spaces and the affordances and constraints they provide for user agency.